Development of History Documentary Learning Media (VIDORA) on the '45 Struggle Monument in Gresik to Enhance Learning Motivation and Student Learning Outcomes in Class XI at Amanatul Ummah Senior High School, Surabaya - Budiarti, Isnaini; Gede Agung, Dewa Agung; Andayani, Endang Sri (Yupa: Historical Studies Journal, 2024)
Ideal history learning is not merely about the process of transferring ideas or knowledge, which students then memorize. Rather, it involves a process of maturation for students to understand identity, self-awareness, and national character through the historical understanding that has been taught. This research has a general goal to produce VIDORA with a local history theme for the 11th-grade Indonesian history subject. The next goal is to improve learning outcomes and learning motivation in 11th-grade history learning at MA Amanatul Ummah. This research uses the ADDIE research model. Based on the research results, it is concluded that VIDORA is highly suitable for use as teaching materials in Indonesian history learning. Based on the research results in schools, there is an increase in learning outcomes from an average of 57.24 to 90.17. This indicates that all students have achieved mastery. Based on the results of the learning motivation questionnaire, a percentage of 82.21% was obtained.